Vibration-Assisted Welding of 42CrMo4 Steel: Optimizing Parameters for Improved Properties and Weldability - Luca, Mihai Alexandru; Roata, Ionut Claudiu; Croitoru, Cătălin; Todi-Eftimie, Alina Luciana (MDPI AG, 2024)
This study advances the vibration-assisted welding (VAW) technique for joining medium-carbon, low-alloy steels, which are typically challenging to weld. Traditional welding methods suggest low linear energy and mandatory pre- and post-heating due to these steels’ poor weldability. However, VAW employs a vibrating table to maintain part vibration throughout the automatic MIG/MAG welding process. This study tested the VAW technique on 42CrMo4 steel samples, achieving satisfactory weld quality without the need for pre- and post-heating treatments. This research revealed that while vibration frequencies between 550 Hz and 9.5 kHz minimally affect the appearance of the weld joint, the oscillation acceleration has a significant impact. The acceleration along the weld axis (ax), combined with the welding speed and vibration frequency, affects the weld surface’s appearance, particularly its scaly texture and size. Lateral acceleration (ay) alters the seam width, whereas vertical acceleration (az) affects penetration depth at the root. Notably, if the effective acceleration (aef) surpasses 40 m/s2, there is a risk of molten metal expulsion from the weld pool or piercing at the joint’s base. The quality of the joints was assessed through macroscopic and microscopic structural analyses, micro-hardness tests in the weld zone, and bending trials. The mechanical properties of the VAW samples were found to be acceptable, with hardness slightly exceeding that of the samples subjected to pre- and post-heating. Moreover, the VAW process significantly reduced energy consumption and operational time. The employed vibration system, with a power rating of 100 W, operates for just a few minutes, resulting in substantially lower energy usage compared to the traditional pre- and post-heating method, which typically requires a 5 kW electric furnace.
Keywords: vibration-assisted welding; VAW; unconventional technology; weldability; vibration; stress relief; mechanical vibration; decreased internal friction